Предмет: Алгебра,
автор: 6vikky9
Помогите решить:
(a+b)(a-b)^3 - (a-b)(a+b)^3
Ответы
Автор ответа:
0
(a+b)(a-b)³-(a-b)(a+b)³=
(a+b)(a-b)((a-b)²-(a+b)²)=
(a+b)(a-b)((a-b+a+b)(a-b-a-b))=
(a+b)(a-b)(2a(-2b))=
-4ab(a²-b²)=
-4a³b+4ab³
(a+b)(a-b)((a-b)²-(a+b)²)=
(a+b)(a-b)((a-b+a+b)(a-b-a-b))=
(a+b)(a-b)(2a(-2b))=
-4ab(a²-b²)=
-4a³b+4ab³
Похожие вопросы
Предмет: Русский язык,
автор: zabud2008
Предмет: Русский язык,
автор: kotya4801
Предмет: Информатика,
автор: Darya060104
Предмет: Биология,
автор: natgavrina2005
Предмет: Алгебра,
автор: Adryshieva